1961
DOI: 10.1002/app.1961.070051706
|View full text |Cite
|
Sign up to set email alerts
|

A study of the fluorescence of cellulosic polymers

Abstract: A spectrophotofluorometer, suitably modified for use with plastics films, was used to study a series of cellulosic polymer films. The chemical structure of the films was found to be related to the wavelength and intensity of the fluorescence emission spectra. Saturated aliphatic esters and ethers were found to possess strong fluorescence maxima at about 350 mμ. Cellulose nitrate exhibits very weak fluorescence at 310 mμ, and a moderate fluorescence maximum appears at 440 mμ for cellulose derivatives containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The method eliminates the distillation procedure used in all modifications of Zeisel's determination and enables quantitative estimation of alkoxyl groups having four to 26 carbons. THE NUMEROUS MODIFICATIONS of the classical Zeisel's method (IS) for the facile determination of the alkoxyl group are restricted to methoxyl and ethoxyl (1,10). The determination of propoxyl and butoxyl involves further modifications of the apparatus and longer procedures (5).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method eliminates the distillation procedure used in all modifications of Zeisel's determination and enables quantitative estimation of alkoxyl groups having four to 26 carbons. THE NUMEROUS MODIFICATIONS of the classical Zeisel's method (IS) for the facile determination of the alkoxyl group are restricted to methoxyl and ethoxyl (1,10). The determination of propoxyl and butoxyl involves further modifications of the apparatus and longer procedures (5).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…There is little information in the literature on the quantitative aspects of the direct examination of polymer films by luminescence techniques. Plitt and Toner (10) have surveyed the literature covering the fluorescence of fibers, rubber, cellulose, polymers, and plastics. They emphasize that the studies reported to date were frequently based on subjective observations of fluorescence in which a broad spectrum of ultraviolet activating energy was used.…”
Section: Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence of 14 polymer types such as polyethylene and poly (phenylacetylene) has been described by Gaehkovskil (166), who suggests its use in molecular weight determinations. Changes in the fluorescence spectra of a variety of cellulosic polymers were correlated with modifications in the chemical structure (384). The effect of styrene monomer on the fluorescence of polystyrene has been measured (32), and a fluorescence polarization method has been used to study the internal structure of dye-labeled polymers in solution (235,353).…”
Section: Miscellaneousmentioning
confidence: 99%
“…21,22 Novel glucose detection techniques also use fluorescent dyes for readout. 20,23−25 However, both cellulose and lignin exhibit autofluorescence, 26,27 a property that was previously used to map changes in cellulose and lignin content and their spatial distribution during biomass pretreatment 28 and to track changes in biomass structure along with localization of cellulolytic enzymes in real time. 6 As we show in this work, the intrinsic fluorescence of biomass can also be exploited to eliminate the need for dyes and labels in cellulolytic assays altogether.…”
mentioning
confidence: 99%